Phenotypic and transcriptomic analyses reveal major differences between apple and pear scab nonhost resistance - Vergne, Emilie; Chevreau, Elisabeth; Ravon, Elisa; Gaillard, Sylvain; Pelletier, Sandra; Bahut, Muriel; Perchepied, Laure (Peer Community Journal)
Nonhost resistance is the outcome of most plant/pathogen interactions, but it has rarely been described in Rosaceous fruit species. Apple (Malus x domestica Borkh.) have a nonhost resistance to Venturia pyrina, the scab species attacking European pear (Pyrus communis L.). Reciprocally, P. communis have a nonhost resistance to Venturia inaequalis, the scab species attacking apple. The major objective of our study was to compare the scab nonhost resistance in apple and in European pear, at the phenotypic and transcriptomic levels.  Macro- and microscopic observations after reciprocal scab inoculations indicated that, after a similar germination step, nonhost apple/V. pyrina interaction remained nearly symptomless, whereas more hypersensitive reactions were observed during nonhost pear/V. inaequalis interaction. Comparative transcriptomic analyses of apple and pear nonhost interactions with V. pyrina and V. inaequalis, respectively, revealed differences. Very few differentially expressed genes were detected during apple/V. pyrina interaction, preventing the inferring of underlying molecular mechanisms. On the contrary, numerous genes were differentially expressed during pear/V. inaequalis interaction, allowing a deep deciphering. Pre-invasive defense, such as stomatal closure, could be inferred, as well as several post-invasive defense mechanisms (apoplastic reactive oxygen species accumulation, phytoalexin production and alterations of the epidermis composition). In addition, a comparative analysis between pear scab host and nonhost interactions indicated that, although specificities were observed, two major defense lines seems to be shared in these resistances: cell wall and cuticle potential modifications and phenylpropanoid pathway induction. This first deciphering of the molecular mechanisms underlying a nonhost scab resistance in pear offers new possibilities for the genetic engineering of sustainable scab resistance in this species. Concerning nonhost scab resistance in apple, further analyses must be considered with the aid of tools adapted to this resistance with very few cells engaged.